Cerebral Artery Diameter in Inbred Mice Varies as a Function of Strain - Qian, Baogang; Rudy, Robert F.; Cai, Tianxi; Du, Rose (Frontiers in Neuroanatomy, 2018)
Many strains of mice are utilized in mouse models of cerebrovascular diseases. Variations in vascular anatomy between these strains has been documented and may influence the phenotype in stroke models. To address inter-strain variations in the circle of Willis anatomy, the diameters of internal carotid, posterior communicating, anterior cerebral and middle cerebral arteries in 144 mice from 32 inbred strains were measured. Arterial diameters were analyzed as a function of animal weight, age, and strain. Variations in the structure of the circle of Willis across strains were observed and noted. While right-sided anterior cerebral arteries were significantly greater in diameter than their left-sided counterparts across most strains, variations in arterial diameter are strain specific. Adult mouse weight was not found to be associated with arterial diameter across strains, suggesting that cerebral artery size is associated with strain independently of weight. This study demonstrates strain dependent variations in the murine circle of Willis, which should be taken into consideration when studying mouse models of cerebrovascular diseases.